A program theory for a continuing professional development program to enhance primary care nurses’ mental health assessment practices - Ariane Girard; Marie-Hélène Lemée; Sarah Lafontaine; Jean-Daniel Carrier; Marie-France Langlois; Hélène Clabault; Luz Piedad Arroyave; Johanie Gagné (Frontiers in Health Services, 2026)
Aim To develop and test the relevance of a program theory underpinning a continuing professional development (CPD) program designed to support primary care nurses in adopting evidence-based mental health assessment practices. Background Primary care nurses play a key role in identifying and responding to mental health needs, yet often report limited confidence and support in conducting assessments. A CPD program grounded in reflective practice and clinical supervision was co-created to address these gaps. Program design included a program theory representing the selected training processes and their expected outcomes. Design Theory-driven evaluation using relevancy testing with a mixed-methods approach. Methods Data collection included questionnaires based on the Ability, Motivation and Opportunity (AMO) framework at baseline, post-training, and 4–6 months follow-up; semi-structured interviews; observational field notes; and a logbook. Research team members analyzed qualitative data thematically and quantitative data descriptively. Results Fourteen primary care nurses from two healthcare centres in Quebec participated ( n = 13 completed). The program enhanced nurses’ ability (knowledge, skills), motivation (confidence and professional engagement), and perceived opportunities at the individual level. Participants reported integrating new practices, including systematic screening, goal-setting, and follow-up, indicating behavioural change. Results suggest reflective and clinical supervision mechanisms that may have explained these outcomes and that enrich the initial CPD program theory. Conclusions A CPD program integrating reflective practice and clinical supervision can strengthen conditions for evidence-based mental health assessment in primary care. Sustained practice change, however, requires alignment with organizational support processes.